2015
DOI: 10.1287/orsc.2015.0973
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Lenient Market Categories

Abstract: Research across disciplines presumes that market categories will have strong boundaries. Categories without well-defined boundaries typically are not useful and do not become institutionalized, so are expected to fade away. In contrast, many contexts contain lenient market categories, or less-constraining market categories, that persist and become important. We argue this fact can be explained by looking at market categories from the producer perspective. Lenient market categories are accepting of many differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 67 publications
8
76
0
Order By: Relevance
“…Categories that are more lenient allow greater flexibility with respect to inclusion than categories that are less lenient; in other words, category boundaries are more porous (Pontikes & Barnett, 2015). Lenient categories are attractive for producers -and presumably for scholars as knowledge producersbecause they can accommodate a greater range of fit (Pontikes & Barnett, 2015).…”
Section: Categories In International Entrepreneurship Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Categories that are more lenient allow greater flexibility with respect to inclusion than categories that are less lenient; in other words, category boundaries are more porous (Pontikes & Barnett, 2015). Lenient categories are attractive for producers -and presumably for scholars as knowledge producersbecause they can accommodate a greater range of fit (Pontikes & Barnett, 2015).…”
Section: Categories In International Entrepreneurship Researchmentioning
confidence: 99%
“…There are a host of individual-level, firm-level events and institutional-level events that can affect firms -for example, foreign travel, a change in leadership, a merger or acquisition, a change in government, a devaluation of currency, or the establishment of (or withdrawal from) a trade agreement -and these may lead to perceptions that the pursuit of a particular opportunity is more or less favorable. Entrepreneurship research suggests that even high profile firm-level successes and failures constitute vital events that signal the quality of subsequent opportunities (Pontikes & Barnett, 2015).…”
Section: Beyond Categorizationmentioning
confidence: 99%
“…For instance, prior research has shown that, in French gastronomy, a large share of producers straddled classical and nouvelle cuisine over the period of study (Durand, ). In the broader restaurant industry, half of the restaurants in San Francisco were assigned to multiple categories/cuisines (Kovács and Hannan, , p. 189); similarly, half of the producers in the software industry appeared to span market categories, as suggested by the 0.5 mean value of fuzziness observed in these categories (Pontikes and Barnett, , p. 1424). Other contexts instead show higher or lower levels of spanning: for example, the mean value of contrast observed in the categories of corporate legal services equals 0.46 (Paolella and Durand, , p. 341) and increases up to 0.7 in the categories of the semiconductor industry (Carnabuci et al, , pp.…”
Section: Discussionmentioning
confidence: 99%
“…Innovations brought by new startup entrants can change the identity and meaning of a product category by prompting reinterpretation of the category to encompass them (G. Hsu, Hannan, & Polos, 2011;Negro, Hannan, & Rao, 2011). Moreover, high-technology product areas can generally be considered lenient categories (Pontikes & Barnett, 2015), given that change and innovation are fundamental characteristics of high-tech. Lenient categories are flexible to change by organizational members (Pontikes & Barnett, 2015), making a startup's choice to enter a new product area formative for the product category as well as the innovation.…”
Section: Boundary-crossing and The Emergence Of Innovation In Startupsmentioning
confidence: 99%
“…Moreover, high-technology product areas can generally be considered lenient categories (Pontikes & Barnett, 2015), given that change and innovation are fundamental characteristics of high-tech. Lenient categories are flexible to change by organizational members (Pontikes & Barnett, 2015), making a startup's choice to enter a new product area formative for the product category as well as the innovation.…”
Section: Boundary-crossing and The Emergence Of Innovation In Startupsmentioning
confidence: 99%